The role of KLF4 in phagocyte activation during infectious diseases - Herta, Toni; Bhattacharyya, Aritra; Hippenstiel, Stefan; Zahlten, Janine (Frontiers in Immunology, 2025)
Phagocytes, including granulocytes (especially neutrophils), monocytes, macrophages, and dendritic cells, are essential components of the innate immune system, bridging innate and adaptive immunity. Their activation and function are tightly regulated by transcription factors that coordinate immune responses. Among these, Krüppel-like factor 4 (KLF4) has gained attention as a regulator of phagocyte differentiation, polarization, and inflammatory modulation. However, its role is highly context-dependent, exhibiting both pro- and anti-inflammatory properties based on environmental signals, cellular states, and the invading pathogen. KLF4 influences monocyte-to-macrophage differentiation and shapes macrophage polarization, promoting either inflammatory or regulatory phenotypes depending on external cues. In neutrophils, it affects reactive oxygen species production and immune activation, while in dendritic cells, it regulates monocyte-to-dendritic cell differentiation and cytokine secretion. Its diverse involvements in immune responses suggests that it contributes to maintaining a balance between effective pathogen defense and the prevention of excessive and potentially harmful inflammation. This review summarizes current knowledge on the function of KLF4 in phagocytes during infections, highlighting its regulatory mechanisms, context-dependent roles, and its impact on immune activation and resolution. Additionally, potential implications for therapeutic interventions targeting KLF4 are discussed.